Differences in kinematic parameters between male and female hammer throw finalists of the World Championship in Daegu in 2011 - Pavlovic, R. (Pedagogy of Physical Culture and Sports, 2020)
Background and Study Aim. Hammer throwing is the most complex athletic throwing discipline with rotational trajectory and strong effect of several different forces that try to disable the projected throwing trajectory. Kinematic parameters are an important segment in the analysis of athletic disciplines, including hammer throw. They are an indicator of influence and often a difference between competitors of different or the same rank of the competition. The aim of the study was to determine the spatial and temporal differences of kinematic parameters between male and female elite hammers. Material and Methods. The study was conducted on sample of 16 Daegu World Championship finalists in 2011, to analyse differences in kinematic parameters between male and female throwers hammer. To obtain the required results, t-test for small independent samples was applied. Results. The data obtained in the study were given as Mean and Standard deviation. Statistically significant differences between male and female finalists were confirmed in the rate of ejection (t=3.684; p<0.004) and the speed of the fourth turn (t=4.396; p<0.002). The male finalists achieved an average ejection velocity of 27.91m/s and the female finalists 27.17m/s, with an average turn speed of 4.67m/s (male) and 4.03m/s (female). Conclusions. The research has shown that significant differences were made between male and female finalists in Daegu in 2011. The causes of differences can be found in length of training, different training process, technical mastery, competitor experience, morphological profile, motor and anatomical structures, movement technique and biomechanical parameters, which were not taken into the research.